Keanekaragaman dan Kelimpahan Semut sebagai Predator Hama Tanaman Padi di Lahan Sawah Organik dan Anorganik Kecamatan Karanganom Kabupaten Klaten - Adhi, Siska Lesiana; Hadi, Mochamad; Tarwotjo, Udi (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
Ants potentially as predators that become natural enemies of insect pests in rice fields with paddy cultivation. This study aims to know the diversity and abundance of ants, the role of ants, the population of ants, and the influence of physical and chemical factors in organic and inorganic rice fields. The ants were collected using pit fall trap method with insect bait, fish meat, and sugar solution. The results showed that the number of species and the number of individuals in organic rice fields was higher (429 individuals, 11 species) than inorganic rice fields (193 individuals, 10 species). In general, the index of diversity in organic rice fields was higher (ranging from 0.73 to 1.65) compared to inorganic rice fields (ranging from 0 to 1.28). The index of evenness in organic rice fields ranged from 0.63 to 0.99 (evenly distributed), whereas in inorganic rice fields ranged from 0 to 0.99 (uneven until evenly distributed). The dominant ants in organic rice fields were Camponotus sp, Solenopsis geminata, Anoplolepis gracilipes, and Paratrechina longicornis, whereas in the inorganic rice fields were Tapinoma sp, Solenopsis geminata, and Camponotus sp. The index of similarity between organic and inorganic rice fields showed a high and very high degree of similarity based on the type of feed. Physical factors of high soil and air humidity environment, high soil and air temperature increased the diversity and abundance of ants in the rice fields ecosystem. Factors soil pH in accordance with the growth of soil Arthropods were neutral or slightly acidic. Chemical factors of organic matter content, Nitrogen (N), the content of C organic, and a high P total content increased the diversity and abundance of ants.Â Keywords: diversity and abundance, ants, organic and inorganic rice fields